Validasi Metode Analisis Kadar Okratoksin A pada Biji Pala (Myristica fragrans Houtt) secara Kromatografi Cair Kinerja Tinggi - hernawaty, Hernawaty; Nurdiana, Indah (Badan Pengawas Obat dan Makanan, 2023)
Nutmeg (Myristica fragrans Houtt) is a superior commodity that is in demand by the European Union, and to enter the export market of the European Union, nutmeg commodities must meet several regulations and requirements, which can be grouped into Legal Requirements and Non-Legal Requirements. On April 1, 2020, there was an additional regulation in the form of the maximum level of Ochratoxins A contained in nutmeg that is allowed is 15 g/kg (EUR-Lex, 2020). So far, an assay of ochratoxin A has not been reported for the scope of nutmeg. Ochratoxin A analysis generally applies the AOAC test method ch.49.6.64 (Assessment of ochratoxin levels in barley) and the AOAC test method Ch 49.6.028 (Assessment of ochratoxin A levels in green coffee), but this method is known to be non-specific for nutmeg because of its spectral characteristics. Ochratoxin A in samples. The purpose of this study was to obtain a valid analytical method for determining levels of ochratoxin A in nutmeg seeds so that it can be widely applied as an important step in meeting the requirements of foreign export standards for ochratoxin A-free nutmeg products. The data used is primary data validation of the analytical method using an HPLC fluorescent detector. Samples were extracted using organic solvents, with PBS pH 7.4 dilution passed to the Immuno Affinity Column (IAC) and eluted with acetic acid-methanol (2:98) and water. The validation results showed specific specificity for nutmeg, linearity 0.9998588 and Vxo 1.40%, RSD precision 2.02%, accuracy 84-87% by adding a certain amount of analyte to the sample matrix to obtain recovery, detection limit 1.59 g/kg and the quantitation limit was 5.82 g/kg. This validated analytical method meets the criteria and can be used to determine levels of ochratoxin A in nutmeg seeds.